From bonds to beliefs: Investigating parent, peer attachment, and growth mindset in private vocational high schools - Azizah, Asti Nur; Herdian, Herdian; Na'imah, Tri; Nurwahidah, Fatin Rohmah (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
This research focuses on investigating the influence of parent and peer attachment on the growth mindset of students enrolled in Private Vocational High Schools in Purwokerto, Indonesia. Stratified proportional random sampling was employed to select participants for this study. Consent was obtained from 235 students who participated. The gender distribution was skewed toward females (57.9%) compared to males (42.1%), with the majority of participants being 16 years old (46.7%). The Inventory of Parent and Peer Attachment (IPPA) was used to measure parent and peer attachment, while the Growth Mindset Scale was employed to assess participants' growth-oriented attitudes. A linear regression analysis was utilized to examine the predictive relationship between mother, father, and peer attachment and growth mindset scores. The results demonstrated significant gender-based variations across the variables studied. Notably, females exhibited significantly higher Mother Attachment scores, indicating a stronger attachment to their mothers. Nonetheless, no considerable gender disparities emerged in Father Attachment scores. Although the distinction in Peer Attachment scores was close to significance (p = 0.053), females displayed slightly higher attachment to peers. A marked gender discrepancy was identified in Growth Mindset scores, with females displaying a notably more positive perspective toward growth and learning opportunities. Furthermore, predictive modeling revealed that Mother Attachment exerted a significant positive impact on Growth Mindset scores (Î² = 0.3), implying that a stronger attachment to mothers corresponded to a more favorable growth-oriented mindset. Similarly, Father Attachment positively contributed to Growth Mindset scores (Î² = 0.25). Additionally, Peer Attachment demonstrated a modest yet positive association (Î² = 0.13). The calculated RÂ² values indicated that both Mother Attachment and Father Attachment collectively accounted for approximately 18% of the variance in Growth Mindset scores, while Peer Attachment contributed to a smaller extent (1%). Collectively, these findings shed light on the intricate relationships between attachment, age, and mindset. They underscore the roles of different attachments in shaping individuals' growth-oriented perspectives and highlight the nuanced gender differences in attachment and mindset. This study provides valuable insights for educators, parents, and policymakers aiming to promote positive growth mindsets among students.